2018
DOI: 10.1371/journal.pone.0191066
|View full text |Cite
|
Sign up to set email alerts
|

The clinical impact of bacteremia on outcomes in elderly patients with pyelonephritis or urinary sepsis: A prospective multicenter study

Abstract: BackgroundBacteremia is common in severe urinary infections, but its influence on the outcomes is not well established. The aim of this study was to assess the association of bacteremia with outcomes in elderly patients admitted to hospital with pyelonephritis or urinary sepsis.MethodsThis prospective muticenter observational study was conducted at 5 Spanish hospitals. All patients aged >65 years with pyelonephritis or urinary sepsis admitted to the departments of internal medicine and with urine and blood cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
2
16
3
Order By: Relevance
“…Mortality at 30 days was 9.4%, similar to that described in previous studies in which bacteremic and non‐bacteremic UTI were included . Mortality from UTI in older patients was associated with age, McCabe >2 and septic shock …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Mortality at 30 days was 9.4%, similar to that described in previous studies in which bacteremic and non‐bacteremic UTI were included . Mortality from UTI in older patients was associated with age, McCabe >2 and septic shock …”
Section: Discussionsupporting
confidence: 79%
“…Demographic, clinical and microbiological patient data were collected on discharge (definitions have been published in a previous study). The study design precludes the researcher from influencing the diagnostic tests requested or the treatment administered.…”
Section: Methodsmentioning
confidence: 99%
“…As the elderly are known to have a higher number of comorbid conditions and poor immune mechanisms, it is plausible to link advanced age with poor prognosis in APN patients. These findings are in accord with most of the published data on APN, mandating it to be considered as a significant risk for complications in PN [14][15].…”
Section: Discussionsupporting
confidence: 89%
“…Published reports varied regarding outcome of UTI cases complicated by sepsis; some authors found worse outcome while others did not. 4,[19][20][21] Morbidity and mortality evaluation was beyond the scope of the present study but we feel outcome evaluation in UTI complicated by bacteramia remains area for further exploration in our setting.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3] UTI, specially pyelonephritis may be complicated by bacteraemia and sepsis. 4,5 Antimicrobials remain the cornerstone for treatment of UTI and increasing antimicrobial resistance, specially extended-spectrum beta-lactamase (ESBL) producing organisms is an ever increasing problem. [6][7][8][9] ESBL-positive organisms are inherently resistant to penicillin and cephalosporin; thus UTI caused by ESBLpositive organism require injectable agents like carbapenems and aminoglycosides or nitrofurantoin, pivmecillinam and fluoroquinolones; many organisms causing UTI are also resistant to these oral agents.…”
Section: Introductionmentioning
confidence: 99%